Commuting in Mumbai, 2008: room for optimism - Badami, Sudhir; Koppikar, Smruti (2004)
The sky bus metro and the high-capacity bus system are innovative methods to ensure efficient, economical and comfortable commuting in Mumbai in 2008 and beyond. - Reproduced.
Keywords: Urban transport - India - Maharashtra; Commuting - India - Maharashtra; Commuting